032 Use of Triptorelin Acetate for Inducing Ovulation and Facilitating Fixed Time Artificial Insemination of Sows Weaned on Small-Scale and Niche Market Pig Farms. (1st December 2016) - Fabi, A. J.; Williams, K. A.; Estienne, M. J.
Abstract: Developing a single fixed-time artificial insemination (FTAI) protocol would benefit small-scale and niche market pork producers by decreasing semen costs and labor associated with detection of estrus. The objective of this study was to test the efficacy of an AI breeding system using triptorelin acetate, a GnRH agonist (OvuGel; JBS United Animal Health, LLC, Sheridan, IN) that induces ovulation. A total of 92 sows (parity, 3.5 ± 0.2; BCS, 2.5 ± 0.08) were weaned (h 0) after a 25.0 ± 0.6 d lactation on five participating small pig farms and allocated to one of four treatment groups: 1) OvuGel applied intravaginally at h 96 and AI at h 120 (n = 23); 2) P.G. 600 (400 IU eCG and 200 IU hCG, Merck Animal Health, Inc., De Sota, KS) applied i.m. at weaning, OvuGel at h 96 and AI at h 120 (n = 23); 3) AI at 0 and 24 h after first detection of estrus (n = 23); and 4) P.G. 600 at weaning, and AI at 0 and 24 h after onset of estrus (n = 23). Treatments 1 and 2 were FTAI protocols with sows being inseminated without regards to estrus onset. Treatments 3 and 4 were consistent with current industry AI practices. The proportion of females displaying estrus by day 7 post-weaning was greater ( P = 0.02) for sows that received OvuGel (93.9 ± 0.07%) compared to sows that did not (81.0 ± 0.07%). There were no effects ( P > 0.05) of P.G. 600 or P.G. 600 × Ovugel on females displaying estrus by day 7. Weaning to estrus interval was decreased ( P = 0.04) for sows that received P.G. 600 (4.9 ± 0.4 d) compared to sows that did not (5.4 ± 0.4 d). There were no effects ( P > 0.05) of Ovugel or P.G. 600 × Ovugel on the weaning-to-estrus interval. There were no effects of P.G. 600, Ovugel or P.G. 600 × Ovugel ( P > 0.1) on pregnancy rate (59%), total litter size (11.8), born live (10.8), or born dead (0.9). These results suggest that FTAI protocols may be employed on small-scale pig farms without compromising reproductive performance.